The UNESCO Open Science Recommendation & Toolkit - A Focus on Africa - Persic, Ana (My University, 2024)
Dr Ana Persic is Programme Specialist for Science Technology and Innovation Policies and Open Science at the UNESCO Headquarters in Paris. An ecologist by training with a Ph.D. in Ecotoxicology, Dr Ana Persic joined UNESCO in April 2006 in the framework of UNESCO's Man and the Biosphere program within the Division of Ecological and Earth Sciences in Paris. She then served as a Science Specialist at the UNESCO Liaison Office in New York from 2011-2018. Her work relates to strengthening the science-policy interface and promoting science, technology, and innovation in implementing the United Nations 2030 agenda for sustainable development and sustainable development goals (SDGs). She coordinated the development of the UNESCO Recommendation on Open Science and is currently working towards its implementation. Questions that were addressed during the session 1. What specific features of the UNESCO Open Science Recommendation make it particularly relevant and beneficial for the African research community, and how can they leverage it effectively? 2. Could you highlight a successful case or example where the UNESCO Open Science Recommendation has played a significant role in advancing open science practices within the African context? 3. In what ways does UNESCO collaborate with local stakeholders, including governments, institutions, and researchers, to promote the adoption and implementation of the Open Science Recommendation in Africa? 4. For those new to the concept of open science, what key resources or tools does the UNESCO Open Science Recommendation offer to guide African researchers in adopting more transparent and collaborative research practices?